2020
DOI: 10.1101/2020.07.13.20141036
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preclinical and first-in-human-brain-cancer applications of [18F]poly-(ADP-ribose) polymerase inhibitor PET/MR

Abstract: We report pre-clinical and first-in-human-brain-cancer data using a targeted poly(ADP-ribose)polymerase1 (PARP1) binding PET tracer, [18F]PARPi, as a diagnostic tool to differentiate between brain cancers and treatment related changes. In a pre-clinical mouse model, we illustrated that [18F]PARPi crosses the blood-brain barrier and specifically binds to PARP1 overexpressed in cancer cell nuclei. In humans, we demonstrated high [18F]PARPi uptake on PET/MR in active brain cancers and low uptake in treatment rela… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…2C). Furthermore, recent clinical data has shown that the utility of [ 18 F]PARPi can be potentially expanded to image brain cancer in patients for treatment monitoring (68). In addition to applying radiolabeled-PARPi in patients for cancer detection, a fluorescent-labeled PARPi, PARPi-FL, was also subjected to clinical studies for the detection of oral carcinoma, and potentially serve as the surgical-margin assessment of epithelial cancer of the upper intestinal tract (69).…”
Section: Radiolabeled Parp Inhibitors: Imaging and Therapymentioning
confidence: 99%
“…2C). Furthermore, recent clinical data has shown that the utility of [ 18 F]PARPi can be potentially expanded to image brain cancer in patients for treatment monitoring (68). In addition to applying radiolabeled-PARPi in patients for cancer detection, a fluorescent-labeled PARPi, PARPi-FL, was also subjected to clinical studies for the detection of oral carcinoma, and potentially serve as the surgical-margin assessment of epithelial cancer of the upper intestinal tract (69).…”
Section: Radiolabeled Parp Inhibitors: Imaging and Therapymentioning
confidence: 99%
“…25 PARP imaging has proven its exceptional clinical merit in several scenarios, specifically for the detection and delineation of oral, brain, pancreatic, and liver cancers, as well as target engagement imaging of different PARP inhibitors. [26][27][28][29][30][31][32] Several PARP1-targeted imaging probes have been developed, with the most prominent among these being PARPi-FL, a fluorescently labeled olaparib analog; [ 18 F]FTT, the first clinically applied PARP radiotracer based on rucaparib. 33 To fully exploit PARP as an imaging biomarker, the development of novel PARP imaging probes with further improved pharmacological profiles is warranted.…”
Section: -23mentioning
confidence: 99%
“…The structure of [ 18 F]PARPi is derived from the scaffold of Olaparib, an FDA-approved PARP1 inhibitor widely used as a therapeutic agent in gynecological malignancies [ 23 ]. [ 18 F]PARPi has been previously shown to bind specifically to tumor areas with a minimal off-target uptake [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%